The effectiveness of reciprocal scaffolding technique on students’ writing skill - Cut Mulia Zuhra; Asnawi Muslem; Bukhari Daud (English Education Journal, 2022)
The objectives of this research were to investigate the effectiveness of using the reciprocal scaffolding technique on students’ writing skills and the students’ responses toward the implementation of the technique in the teaching and learning process at the second-year student of State Junior High School 1 Kutamakmur, North Aceh. The samples for this study were drawn in two customized groups using a random sampling approach with class VIII/b as the experimental group and class VIII/d as the control group forming a total of 52 students. The data for this study were gathered using a test and a questionnaire. The data were analyzed to determine the difference in the t-test scores between the two groups. The statistical results showed that the control group’s mean pre-test score was 50.15, which was lower than the experimental group’s 51.69. Meanwhile, the mean score of the experimental group in the post-test was 70.88, which was higher than the control group’s 58.34. The significant value for both groups in the post-test was 0.00, which is less than 0.05. Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. It indicates that teaching writing while employing reciprocal scaffolding more effectively improves the students’ writing than teaching without it. In addition, the questionnaire that was presented to the experimental group revealed that the students gave positive responses toward the use of reciprocal scaffolding techniques in teaching writing.